KEPASTIAN HUKUM TERHADAP EKSEKUSI TERPIDANA MATI DALAM HUKUM PIDANA INDONESIA - Ibnu Sya’ban Syah J; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Legal certainty regarding the execution of death row in Indonesian criminal law is not regulated regarding the period of execution of decisions that have permanent legal force. This makes the time limit for execution even more unclear because there is no definite legal basis. In this way the law also seems to allow uncertainty regarding the execution deadline. The long delay has reached many years even though the verdict has permanent legal force and there are convicts who did not take extraordinary legal remedies or file for clemency. Detention in a prison that lasts a long time and is not certain to indicate a conflict with the principle of legal certainty.This research is a normative legal research. Legal research carried out by examining mere library materials or secondary data, can be called normative legal research or library legal research (in addition to sociological or empirical legal research that primarily examines premiere data). This research uses a research methodology on legal principles.Based on the results of the study it can be seen that the legal certainty of the execution of death row in Indonesian criminal law up to now violates many human rights both in its regulation and application. The delay on protracted executions has a close relationship with legal certainty. This can be seen from how long the convict must wait in prison to be executed and whether the death row inmate will be executed or not. The uncertainty in the execution of capital punishment certainly is contrary to the legal certainty of a just criminal law enforcement process. Ideal arrangements regarding the implementation of capital punishment should be immediately carried out in accordance with predetermined rules, so that the creation of legal certainty for the execution of death row inmates until the future.Keywords: Legal Certainty, Death Penalty, Execution